Statin prescribing pattern and the outcomes for acute coronary syndrome as primary and secondary prevention: a comprehensive review - Dewi, Pramitha Esha Nirmala; Chairani, Farahdina; Himawan, Wahyu (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Cardiovascular disease is the highest rate of total burden non-communicable disease worldwide in these 5 recent years. Reducing the LDL-c level is closely related to reducing the risk of cardiovascular events recurrences among Acute Coronary Syndrome (ACS) patients. This study aims to explore the statin prescribing pattern among the ACS population and population at risk of ACS and to sum up the reported clinical outcomes, cost-effectiveness, or quality of life-related to statin utilization. The literature searching was conducted by using PubMed and Scopus databases from January 2020 to December 2021. Ten eligible studies were included, examining outcomes such as Major Adverse Cardiovascular Events (MACE), quality of life, and cost-effectiveness. Atorvastatin emerged as the most frequently prescribed statin for both primary and secondary prevention. In high-risk ACS populations, the delayed or underutilization of high-intensity statins led to suboptimal cardiovascular outcomes. Conversely, early administration, particularly within 48 hours post-event or post-PCI, significantly reduced MACE. Importantly, low to moderate intensity statin regimens showed cost-effectiveness primarily among low-risk ACS groups only when treatment was fully subsidized. In settings without government coverage, statin inaccessibility may affect the increased of recurrent events and elevated healthcare costs. The strategic use of statins—especially timely initiation and risk-based intensity selection—offers measurable benefits in reducing cardiovascular events. However, the lack of universal healthcare coverage for statin therapy in low- to middle-income settings presents a substantial barrier to cost-effective care, particularly for high-risk individuals. These findings underscore the need for policy interventions and expanded access to guideline-directed statin therapy.